2010
DOI: 10.1007/s10029-010-0686-8
|View full text |Cite
|
Sign up to set email alerts
|

One-year follow-up after incisional hernia treatment: results of a prospective randomized study

Abstract: Mesh repair is the first-choice technique for incisional hernia treatment. The results of the "Sublay" technique are better than the "Onlay" technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
92
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 27 publications
6
92
1
1
Order By: Relevance
“…This study is almost comparable to present study. 12 Weber et al conducted study on 550 patients and noticed recurrence in 22(12.2%) patients in onlay technique and 53(14.4%) in sublay technique as patients considered in sublay technique (369). So, recurrence rate is more in sublay technique.…”
Section: Discussionmentioning
confidence: 99%
“…This study is almost comparable to present study. 12 Weber et al conducted study on 550 patients and noticed recurrence in 22(12.2%) patients in onlay technique and 53(14.4%) in sublay technique as patients considered in sublay technique (369). So, recurrence rate is more in sublay technique.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that influence recurrences in hernia surgery include inadequate surgical technique, size of the hernia, obesity, wound site infection, cigarette smoking, diabetes, COPD, advanced age, and the use of steroid. [18][19][20][21][22] Recurrence rate has been reported in the literature as 1-22% for incarcerated inguinal hernias [23,24] and as 1-10% for incarcerated femoral hernias. [25] In the present study, recurrence was determined in totally 8 (4.2%) cases; the recurrence rate was highest in inguinal hernia (n=6, 5.9%) as compared to all hernia types.…”
Section: Discussionmentioning
confidence: 99%
“…Wound complications such as infection, seroma, and hematoma increase the risk of recurrence by 4.1, 3.4, and 3.5 times, respectively (15). In a randomized prospective study, Venclauskas et al (18) reported that onlay mesh repair requires less time than sublay mesh repair. Moreover, they reported that sublay mesh repair had a lower postoperative complication rate.…”
Section: Incisional Hernia Remains a Major Problem After Laparotomymentioning
confidence: 99%
“…Den Hartog et al (20) reported recurrence rates of 7.4% by onlay mesh repair and 13.6% by sublay mesh repair. Moreover, Venclauskas et al (18) reported recurrence rates of 10.5% using onlay mesh repair and 2% using sublay mesh repair. In a meta-analysis, Mathes et al (22) reported no difference in recurrence rates.…”
Section: Incisional Hernia Remains a Major Problem After Laparotomymentioning
confidence: 99%